Development of dystrophin-based biomarker for penaeid shrimps / Raji Fatimah Omotayo - Raji Fatimah , Omotayo (2019)
The shrimp aquaculture industry is constantly hounded by diseases, which cause an astounding loss of crops and money. Lack of early disease detection and diagnostic methods, both in the past and currently, for emerging diseases, contributes greatly to this. Great strides have, however, been made in developing detection and diagnostic methods for the oldest and most common shrimp viruses, which include White Spot Syndrome Virus (WSSV). DNA-based methods are commonly used for detection, diagnosis and surveillance, these days. The dystrophin gene is a muscle gene which plays a crucial role in maintaining muscle rigidity. Mutations in this gene give rise to dystrophies which are characterized by muscle wasting, and are, eventually, fatal. Dystrophin exists in all vertebrates and has been found and characterized in only a few invertebrates. It has been characterized in two shrimp species, Macrobrachium rosenbergii and Penaeus monodon. In one of those studies, its expression was found to be affected in WSSV infected M. rosenbergii. This study sought to identify the dystrophin gene in Litopenaeus vannamei and then, design a biomarker for disease detection, based on the dystrophin gene. Total RNA was extracted from the muscles of healthy L. vannamei and then, reverse transcribed to cDNA which was then used for PCR, using primers designed from dystrophin sequences of different organisms. The biomarker was then designed from a conserved region of the gene, and was used in quantitative real-time PCR, to quantify the expression of the gene in WSSV and AHPND- challenged P. monodon. The expression of dystrophin was found to be altered in the challenged shrimps, following different patterns for both infections. This finding makes the dystrophin gene a suitable diagnostic biomarker and a possible predictive biomarker for penaeid shrimps.